The entrepreneurial league table of German regions 1895 and 2019 - Michael Fritsch; Maria Greve; Michael Wyrwich (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2024)
We describe and analyze the long-term development of self-employment in German regions between 1895 and 2019. Based on rankings ("league tables") for the two years we identify those regions where the relative level of self-employment significantly increased ('leapfroggers'), and those where the level of self-employment as compared to other regions deteriorated ('plungers'). Germany is a particularly interesting case due to the turbulent history of the country over the 20th century that includes two lost World Wars, occupation by foreign armies, forty years of division into a capitalist and a socialist state, as well as reunification and shock transformation of the eastern part to a market economy. While there is some persistence of regional self-employment despite all the disruptive changes, we also find and discuss considerable changes of regional levels of entrepreneurial activity.
Keywords: L26; R11; O52; 330; Entrepreneurship; self-employment; regional dynamics